An Intriguing Work of Engineering and Architecture: The Collonnade Bridge in Piešt’any - Moravčíková, Henrieta (Docomomo Journal, 2011)
The period around the year 1930 could be termed the culminating point with respect to the Modern architectural avant-garde in Slovakia. It was then that the concepts emerged from the most important works, the first Slovak architectural journals began to be published, the School of Applied Arts opened, as a Slovak variant of the German Bauhaus, and an entire range of other artistic and social initiatives indicated that Slovakia’s cultural environment could not only absorb avant-garde impulses, but develop them in a unique way. It was precisely at this moment that the history of one of the most famed bridges in Slovakia, the Colonnade Bridge in Piešt’any, began to be written.